Adaptive clinical trials: conclusion and future directions - Shyr, Yu (Henry Stewart Talks, 2017)
Definition of an adaptive clinical trial, Three major types of trials, Three types of clinical endpoints, Biomarker-adaptive clinical trials design, Recently FDA approved drugs, Prognostic marker, Predictive marker, Enrichment designs, Biomarker-stratified design, Randomized hybrid design, Umbrella and basket trials, Examples of phase I, II, and III trials